A Study of Glutathione S-transferase pi Expression in Central Nervous System of Subjects with Amyotrophic Lateral Sclerosis Using RNA Extraction from Formalin-Fixed, Paraffin-Embedded Material - Usarek, Ewa; Gajewska, Beata; Kaźmierczak, Beata; Kuźma, Magdalena; Dziewulska, Dorota; Barańczyk-Kuźma, Anna (Neurochemical research, 2005)
The expression of glutathione S-transferase pi (GST pi), an enzyme responsible for inactivation of a large variety of toxic compounds was studied in spinal cord, motor and sensory brain cortex obtained from patients who died in the course of amyotrophic lateral sclerosis (ALS). The studies were performed on formalin-fixed, paraffin-embedded (FFPE) and freshly frozen tissues. The method of RNA isolation from FFPE was modified. A significant decrease of GST pi-mRNA expression was found in cervical spinal cord and motor brain cortex of ALS subjects comparing to analogue control tissues (P<0.01), as well as in motor cortex of ALS subjects comparing to their sensory cortex (P<0.05). In spinal cords the decrease in GST pi-mRNA expression was accompanied by a decrease of GST pi protein level. Results indicated lowered GST pi expression on both mRNA and protein levels in the regions of nervous system affected by ALS. The non-properly inactivated by GST toxic electrophiles and organic peroxides may thus contribute to motor neurons damage.